X-men: mutant genesis ebook Mutant genesis - special. - Claremont, Chris (X-Men (1991)., 2011)
Collects X-Men (1991) #1-7. The mutant terrorist Magneto again threatens the world, and only the X-Men can stop him! And should they survive this confrontation, the villainous Omega Red is waiting in the wings!